Pemilihan serentak petinggi kampung tahun 2018 di Kecamatan Long Hubung Kabupaten Mahakam Ulu: The 2018 Simultaneous Election of Village Heads in Subdistrict of Long Hubung, Mahakam Ulu District - Andreanus Ding (JOURNAL OF GOVERNMENT SCIENCE, 2020)
The purpose of this research is to examine the implementation of Regional Regulation Number 9/2017 on the Selection, Appointment, and Dismissal of Village Head in Mahakam Ulu Regency by using the case of the 2018 simultaneous direct election of Village Heads (Petinggi) in Long Hubung sub-District. This research employed purposive sampling technique in data collection, and descriptive qualitative in analysis. The results show that while such a Regional Regulation has been implemented, it has not proved optimal yet. This is due to the fact that inhibiting factors are still found in the implementation of simultaneous election of Village Heads in Long Hubung sub-district, causing one out of four villages to postpone the elections. Lack of communication, information, and coordination between the election committees in sub-district and at village levels caused several problems. More specifically, outdated list of eligible voters, allowing outsiders with improper documents to vote, and similar issues, became the source of vote cheating by high-ranking candidates.  Keywords: village election, village heads(petinggi), policy implementation